Taxes and benefits: two distinct options to cheat on the state? - Martin Halla; Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2008)
While there is an extensive literature on tax evasion a further aspect of cheating on the state, namely benefit fraud, has gained relatively modest attention in the economic literature. This paper seeks to fill this gap. We explore differences between benefit fraud and tax evasion due to differing social norms. We define the concepts of benefit morale and tax morale as the motivation to abstain from cheating on the state via these two offenses. Our multilevel analysis, based on a large micro data set of respondents from 29 OECD member countries, shows that benefit morale and tax morale have different determinants at an individual-level and respond differently to fiscal policy measures.
urn:nbn:de:101:1-2008061392
Keywords: H20; 330; Tax; subsidies; tax evasion; benefit fraud; welfare fraud; tax morale; benefit morale; social norms; multilevel analysis; Steuermoral; Steuervermeidung; Sozialhilfe; Betrug; Schätzung; Österreich